Chemical analysis, repellent, larvicidal, and oviposition deterrent activities of plant essential oils against Aedes aegypti, Anopheles gambiae, and Culex quinquefasciatus - Abbas, Muhammad Ghazanfar; Binyameen, Muhammad; Azeem, Muhammad; Majeed, Shahid; Sarwar, Zahid Mehmood; Nazir, Abdul; Sharif, Mahar Muhammad Imran; Parveen, Amna; Mozūratis, Raimondas (Frontiers in Insect Science, 2025)
Plant-based essential oils have gained attention as a natural alternative for controlling mosquitoes due to their repellent, larvicidal and oviposition deterrent properties. We tested repellent, larvicidal, and oviposition deterrent effects of essential oils (EOs) of Mentha spicata (L.), Ocimum basilicum (L.), and Abutilon indicum (L.) against three mosquito species (Diptera: Culicidae) including Aedes aegypti (L.), Anopheles gambiae s. l. Giles, and Culex quinquefasciatus Say by using contact-based technique. In screening bioassays, M. spicata I, M. spicata II, O. basilicum I, O. basilicum II, and A. indicum EOs showed higher repellency against Cx. quinquefasciatus as compared to Ae. aegypti and An. gambiae when tested at 33.3 μg/cm2. In time-span bioassays performed at 33.3 μg/cm2, EO of M. spicata I exhibited 100% repellence up to 45, 30, and 75 min against Ae. aegypti, An. gambiae, and Cx. quinquefasciatus, respectively. Interestingly, at this tested dose, M. spicata I and M. spicata II showed higher repellence compared to DEET against Ae. aegypti and Cx. quinquefasciatus after 45 and 75 min, respectively. Their repellency was observed up to 150 and 210 min against Ae. aegypti and Cx. quinquefasciatus, respectively. In larvicidal bioassays, M. spicata I EO proved more toxic against 2nd instar larvae of Ae. aegypti, An. gambiae, and Cx. quinquefasciatus (LC50 = 11.0, 42.9, and 12.6 mg/L, respectively) compared to other tested EOs. In oviposition bioassays, M. spicata I exhibited the highest activity, showing 60%, 46%, and 79% oviposition deterrence against Ae. aegypti, An. gambiae, and Cx. quinquefasciatus, respectively, tested at a dose of 600 µg/cm2. Major compounds of M. spicata I, M. spicata II, O. basilicum I, and O. basilicum II EOs were piperitenone oxide (38.8%), piperitone oxide (35.4%), estragole (55.3%), and linalool (43.8%), respectively. In conclusion, M. spicata EO could be used to control mosquitoes and their bites.